(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Design and Good Living are interconnected concepts that promote quality of life, especially in vulnerable territories. Design acts as a tool for social change, creating aesthetic and functional solutions that meet physical, emotional, and cultural needs. Buen Vivir, based on the Andean indigenous worldview, prioritizes harmony between humans, nature, and the universe, focusing on peripheral communities. This article presents examples of the resignification of spaces in the global south, based on the theory of Biophilia by Edward Wilson, Stephen Kellert and Alberto Acosta, showing how biophilic design restores the human connection with nature, favoring Buen Vivir.